Kyai’s Leadership in Improving the Quality of Salafiyah Pesantren Education - Fauzi, Anis; Gunawan, Agus; Mu'minin, Himayatul (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
There is a tendency for Salafiyah Pesantren to experience a decrease in the number of students, and many are facing a decline in the scientific quality of their alums and current students. Culturally, the erosion of Salafiyah traditions has become increasingly apparent, ranging from the weakening sense of ta’zhim toward the Kyai, reduced learning persistence accompanied by tarikat rituals—fasting, wirid, and others—to diminishing belief in karomah and barakah once deeply embedded among students. This study aims to explain the leadership and management patterns employed by the Kyai in enhancing the educational quality of the Cidanghiang Salafiyah Pesantren. The research employed a qualitative approach in which data were collected through interviews, observations, documentation, field notes, and triangulation. The findings indicate that the Kyai of the Cidanghiang Salafiyah Pesantren exercises charismatic informal authority combined with managerial competencies, demonstrating not only innate leadership talent but also a strategic and future-oriented vision for advancing Salafiyah-based educational services. In practice, the Kyai fulfils managerial roles involving planning, organizing, implementing, evaluating, and controlling the core academic and non-academic processes of the pesantren.